STUDENTS’ PERCEPTIVE OF ENGLISH ONLINE LEARNING DURING COVID-19 PANDEMIC - Zahro, Ianatuz (ETERNAL (English, Teaching, Learning, and Research Journal), 2021)
This study aimed to know the students’ perspective of English online learning during Covid-19 pandemic regarding readiness aspect, learning performance, and the obstacles students face in learning distance. This study used qualitative research and it was conducted from September until January in 12 meetings of distance learning using online applications. The questionnaires were given to 42 first-semester students of social faculty of IKIP PGRI Jember. The result showed that almost all students had good preparation before joining English online learning. However, students faced some main problem during online learning: unstable internet connection, losing their concentration starring at the screen of hand-phone or computer, and spending more money to buy internet quota. In conclusion, there were students’ perspective in English online learning, i.e. 1) students have good English motivation motivation; they prepare the equipment needed before joining the online learning. 2) The lecture’s style to teach English, students prefer to use the bilingual method to make them easier to understand the materials. 3) Google meet and zoom applications are the most chosen application used in virtual meetings because they provide good interaction between teachers and students. 4) The obstacles in online learning faced by students. i.e. unstable internet, lose concentration.